Cover Image, Volume 7, Issue 4. (16th June 2017) - Hermans, Susanne M.A.; Pfleger, Christopher; Nutschel, Christina; Hanke, Christian A.; Gohlke, Holger
Abstract : The front cover image, by Susanne M.A. Hermans et al., is based on the Advanced Review Rigidity theory for biomolecules: concepts, software, and applications, DOI:10.1002/wcms.1311 . Abstract : The front cover image, by Susanne M.A. Hermans et al., is based on the Advanced Review Rigidity theory for biomolecules: concepts, software, and applications, DOI:10.1002/wcms.1311 .